G456(P) Waving the red flag: characteristics of children who require critical care for life-threatening asthma and wheeze. (12th March 2018) - Chau, SY; Brown, C; Hurley, MN
Abstract : Aim: The RCPCH report 'State of Child Health' (2017) reported the prevalence of deaths due to asthma in the UK as among the highest in Europe. Local differences in these indices suggest varying standards of care may be an underlying factor. As part of an evaluation of the hospital-wide asthma service, we aimed to identify characteristics of children who required critical care in order to determine if the needs of this high-risk group are being met. Method: The PICU database was interrogated to identify children who had required critical care for wheeze or asthma. Characteristics of the critical care stay were retrieved from the clinical record to identify characteristics locally of children who experience life-threatening episodes of acute respiratory distress. Results: Fifty-four children were admitted on 72 occasions with wheeze. 32 children with asthma, 19 children with wheeze. Three children, admitted on 4 occasions, were excluded for alternative diagnoses. Unsurprisingly children with asthma were older (mean 92.54. sd 53.8 months) than children with wheeze (mean 24.79, sd 17.52 months). Children with asthma were each admitted to PICU more frequently than children with wheeze (mean 1.97, sd 1.43 vs mean 1.26, sd 0.56). For the 68 included episodes, respiratory support was needed on 26 occasions (formal ventilation on 12). In 49% of cases children lived in a household where a family member smoked (15 asthma; 5 wheeze). On 15 occasions household smoking status was not documented. In 16 cases of asthma there were documented social concerns (compliance, clinic attendance, formal safeguarding) compared to only 1 case of the 19 children with wheeze. Children in the asthma group came from larger families with 3.5 children (IQR 2, 4 max 11) per family compared to 2.4 children (IQR 1, 3 max 7) in the wheeze group. Conclusion: Children with the most severe episodes requiring critical care often present on multiple occasions and come from large families with household smoking exposure. Concerns regarding the inappropriately low priority of the children's health by their families are common.